Adrenal (Pro)renin Receptor Expression and Serum Soluble (Pro)renin Receptor Concentration in Primary Aldosteronism. (28th September 2020) - Watanabe, Daisuke; Morimoto, Satoshi; Morishima, Noriko; Kato, Yoichiro; Nagashima, Yoji; Shibata, Noriyuki; Ichihara, Atsuhiro
Abstract : The (pro)renin receptor [(P)RR] is a multifunctioning protein playing roles in various pathological conditions. A soluble form of (P)RR [s(P)RR] has been considered a biomarker for (P)RR expression in tissues. Expression of (P)RR has been described in aldosterone-producing adenoma (APA), but the roles of (P)RR have yet to be fully determined. This study investigated the significance of (P)RR and serum s(P)RR concentrations in patients with APA. We evaluated associations between (P)RR expression and expression of CYP11B2, an aldosterone synthase, and aldosterone production by the adrenal glands and assessed the relationships between serum s(P)RR concentration and background factors. (P)RR colocalized with CYP11B2 and expression levels of (P)RR were positively associated with those of CYP11B2 in APA tissues. (P)RR immunoreactivity in these tissues correlated positively with plasma aldosterone concentrations (PAC) and urinary aldosterone excretion. Also, in APA, (P)RR mRNA abundance was positively correlated with β -catenin mRNA abundance. Significant positive correlations were identified between serum s(P)RR concentration and plasma glucose, hemoglobin A1c, and serum creatinine levels, but not with PAC (in either peripheral vein or adrenal vein) or adrenal (P)RR expression level. This study showed that (P)RR expression level correlates with CYP11B2 expression in APA tissues and PAC and urinary aldosterone excretion, suggesting that (P)RR expression may contribute to aldosterone synthesis via CYP11B2 activation in APAs, although serum s(P)RR concentration failed to show any significant relationship with adrenal (P)RR expression. Adrenal (P)RR activity might offer a therapeutic target in the treatment of PA, although this issue needs to be investigated in future studies.